Physicochemical properties of Indonesian lignite continuously modified in a tunnel-type microwave oven for slurribility improvement. (15th June 2015) - Cheng, Jun; Zhou, Fan; Wang, Xin; Liu, Jianzhong; Zhou, Junhu; Cen, Kefa
Abstract: Indonesian lignite was continuously modified in a tunnel-type microwave oven to improve its slurribility. The maximum solid concentration of coal–water slurry (CWS) prepared from modified lignite increased from 41.6 wt.% to 54.0 wt.% with an enhanced rheological behaviour. The contact angle, oxygen functional groups, molar ratio of methylene to methyl, paramagnetic centres of modified lignite were analysed on contact angle analyzer, Fourier transform-infrared spectroscopy, X-ray photoelectron spectroscopy, electron paramagnetic resonance spectroscopy to clarify the modification mechanisms. The molar ratio of the methyl group to the methylene group of the modified lignite decreased, resulting in shortened aliphatic chains and condensed aromatic rings. The unpaired electrons concentration of the modified lignite increased, implying that the coal rank was upgraded. As a result, the contact angle of the modified lignite increased and oxygen functional groups with high hydrophilicity decreased, leading to an improved CWS property.